Brain derived neurotropic factor (BNDF) DNA methylation in schizophrenia and its association with antipsychotic use - Tokhi, Elham (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Epigenetic mechanisms regulate gene functions without causing a change in the nucleotide sequence of DNA. Brain-derived neurotrophic factor (BDNF) is a neurotrophin that regulates synaptic transmission, plasticity and has essential role in neurodevelopment. Collected evidences suggest that epigenetic changes in BDNF gene are related to pathophysiology of psychiatric disorders such as schizophrenia. Therefore, the BDNF DNA methylation and the effect of methylation on BDNF gene expression in the peripheral blood of schizophrenic patients were assessed in this study. In addition, the role of DNA methylation on antipsychotics was studied. Overall, 118 (88 male and 30 female) schizophrenic patients and 122 (92 male and 30 female) healthy controls were included in the study and methylation status was investigated using methylation specific PCR. The results revealed that there was no significant change in DNA methylation status between schizophrenia patients and controls in this study. However BDNF DNA methylation showed positive significant correlation with positive symptoms of schizophrenia as well as antipsychotics use. In addition, DNA methylation level was correlated with gender and the difference was more significantly prominent in male. To conclude, although there was no difference in BDNF gene methylation status in this group of schizophrenia patients as compared to healthy controls, there was significant association between sex vs. methylation status and positive symptoms of schizophrenia vs. methylation status.